INCREASING GREEN BUSINESS LITERACY THROUGH ICT (INFORMATION AND COMMUNICATIONS TECHNOLOGY) FOR MSME BUSINESS PLAYERS - Ervani, Eva; Effendi, Nury; Indupurnahayu, Indupurnahayu; Intanie Dewi, Vera; Shinta Aminda, Renea; Samuel Sapulette, Militcyano (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Green business through ICT (Information and Communications Technology) is one way to make resources efficient. One example of the application of ICT in business is buying and selling that is done online or online business. The limited understanding of MSME business actors regarding the application of ICT in green business activities prompted the team of authors to carry out socialization by holding a training (workshop) "Increasing MSME competitiveness through green business". One of the topics was “Green business through ICT”. The purpose of this training is to increase the understanding and literacy of MSME actors regarding the application of ICT in green business activities. The method of the workshop is lectures, training, discussions, and questions and answers between speakers and workshop participants who are MSME actors in the cities of Bandung and Bogor. The results of the workshop activities show an increase in literacy, understanding, and insight into green business through ICT from MSME business participants. Through this workshop, information was also obtained that not all MSME actors have implemented green business through ICT in their business. From the results of the interaction during the implementation of the workshop, information was obtained that all participants stated that the workshop activities provided benefits.